Seabird attendance and incidental mortality at shrimp fisheries in Golfo San Jorge, Argentina - Gonzalez Zevallos, Diego Ricardo; Yorio, Pablo Martin; Svagelj, Walter Sergio (Marine Ecology Progress Series)
Many seabirds are attracted to trawl vessels to make use of fishery waste, and often this attraction results in increased incidental mortality. We assessed seabird attendance and associated incidental mortality at the Argentine red shrimp Pleoticus muelleri trawl fishery in Golfo San Jorge, Argentina. Information on seabird numbers was gathered in the autumn and winter 2006 and spring 2008, while information on seabird incidental captures was obtained for the period 2005-2007. Eighteen seabird species attended vessels, and the 2 most frequent and abundant seabirds (percent occurrence, median no. haul -1) were the kelp gull Larus dominicanus (>94%, <100) and blackbrowed albatross Thalassarche melanophrys (>94%, <55). Seabird numbers were significantly lower in winter than the other 2 seasons and highest during discarding activities. Species incidentally killed in nets were the Magellanic penguin Spheniscus magellanicus and imperial cormorant Phalacrocorax atriceps, with a mean capture rate of 0.048 birds haul-1, and for both species, mortality decreased with distance to the coast. Considering the fishery's fishing effort during each month, the estimated total mortality in the study period was 895 (95% CI: 572 to 1339) penguins and 172 (95% CI: 69 to 305) cormorants. Over 95% of the recorded mortality occurred in 2005, the year when the trawling moratorium generally implemented in the area was not enforced. No interactions with warp cables were recorded. Results highlight the relevance of complying with the current moratorium scheme, as adjusting it to the penguin and cormorant breeding seasons may by a potentially effective management tool. The proximity to the coast of the recorded incidental mortalities indicates the need to reevaluate the spatial design of the park and/or the definition of management actions beyond the boundaries of the Marine Protected Area. Fil: Gonzalez Zevallos, Diego Ricardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina ...